Local Dexamethasone Administration Delays Allogeneic Islet Graft Rejection in the Anterior Chamber of the Eye of Non-Human Primates. (May 2022) - Tun, Sai Bo Bo; Chua, Minni; Tan, Gavin Siew Wei; Leibiger, Ingo; Ali, Yusuf; Barathi, Veluchamy Amutha; Berggren, Per-Olof
Pancreatic islet transplantation into the anterior chamber of the eye (ACE) has been shown to improve glycemic control and metabolic parameters of diabetes in both murine and primate models. This novel transplantation site also allows the delivery of therapeutic agents, such as immunosuppressive drugs, locally to prevent islet graft rejection and circumvent unwanted systemic side effects. Local intravitreal administration of micronized dexamethasone implant was performed prior to allogeneic islet transplantation into the ACEs of non-human primates. Two study groups were observed namely allogeneic graft without immunosuppression (n = 4 eyes) and allogeneic graft with local immunosuppression (n = 8 eyes). Survival of islet grafts and dexamethasone concentration in the ACE were assessed in parallel for 24 weeks. Allogeneic islet grafts with local dexamethasone treatment showed significantly better survival than those with no immunosuppression (median survival time- 15 weeks vs 3 weeks, log-rank test p<0.0001). Around 73% of the grafts still survived at week 10 with a single local dexamethasone implant, where the control group showed no graft survival. Dexamethasone treated islet grafts revealed a good functional response to high glucose stimulation despite there was a transient suppression of insulin secretion from week 8 to 12. Our findings show a significant improvement of allografts survival in the ACE with local dexamethasone treatment. These results highlight the feasibility of local administration of pharmacological compounds in the ACE to improve islet graft survival and function. By eliminating the need for systemic immunosuppression, these findings may impact clinical islet transplantation in the treatment of diabetes, and the ACE may serve as a novel therapeutic islet transplantation site with high potential for local pharmacological intervention.